MENGHARMONISASIKAN TRADISI DAN MODERNITAS Penerapan Filsafat Progresivisme di Pesantren - Amrullah, Arfan; Lail, M. Khabib Jamlalul; Khobir, Abdul; Rafi, Muhammad (Muta'allim: Jurnal Pendidikan Agama Islam, 2025)
This study examines the harmonization of tradition and modernity through the application of progressivism philosophy in Islamic boarding schools (pesantren) as Islamic educational institutions adapting to global dynamics. Employing a qualitative method based on questionnaires, this research explores the perspectives of students (santri) and pesantren administrators regarding integration strategies, challenges, and the impact of progressivism implementation within the pesantren educational system. The findings reveal a high level of awareness among pesantren educational actors concerning the urgency of curriculum reform to align with contemporary demands. Nevertheless, the application of progressivism faces significant challenges, including limited technological resources, cultural resistance from surrounding communities, and insufficient readiness of educators to adopt modern teaching approaches. The integration of technology, particularly through digital applications in Qur'an memorization, has proven to be an effective instrument in bridging traditional heritage with modern demands. This study recommends strengthening educators’ capacities, developing technological infrastructure, and fostering multi-stakeholder collaboration to accelerate pesantren’s adaptation as an inclusive, adaptive, and relevant Islamic education model in the era of globalization, while preserving its traditional roots.Abstrak Penelitian ini mengkaji harmonisasi tradisi dan modernitas melalui penerapan filsafat progresivisme di pesantren sebagai lembaga pendidikan Islam yang tengah beradaptasi dengan dinamika global. Dengan menggunakan metode kualitatif berbasis kuesioner, studi ini mengeksplorasi pandangan santri dan pengelola pesantren mengenai strategi integrasi, kendala, serta dampak implementasi progresivisme dalam sistem pendidikan pesantren. Hasil temuan menunjukkan tingginya kesadaran aktor pendidikan pesantren akan urgensi pembaruan kurikulum agar selaras dengan kebutuhan zaman. Namun demikian, penerapan filsafat progresivisme dihadapkan pada tantangan signifikan, seperti keterbatasan sumber daya teknologi, resistensi budaya dari lingkungan sekitar, serta minimnya kesiapan pendidik dalam mengadopsi pendekatan pembelajaran modern. Integrasi teknologi, khususnya melalui aplikasi digital dalam pembelajaran Al-Qur’an, terbukti menjadi instrumen efektif dalam menjembatani antara warisan tradisional dan tuntutan modernitas. Penelitian ini merekomendasikan penguatan kapasitas pendidik, pengembangan infrastruktur teknologi, serta kolaborasi multipihak guna mempercepat adaptasi pesantren sebagai model pendidikan Islam yang inklusif, adaptif, dan relevan di era globalisasi, tanpa menghilangkan akar tradisi yang menjadi identitasnya